Kajian Instrumen Rekayasa Sosial dalam Mengontrol Produksi Berita pada Media Online Menurut Undang-Undang No 40 Tahun 1999 Tentang Pers - Yosefina Daku (Warmadewa Press, 2024)
In Indonesia, the role of the media in shaping public opinion is significant, making the regulation of news production even more important. Policy formulations that are considered ineffective in maintaining the quality of information and controlling news production can affect the social, security and political stability of a country. The interpretation of freedom of the press or freedom of expression is not an open space for producing news that is untrue or incomplete. The Law on the Press has become the main guideline in regulating journalistic practices. However, to what extent is the press law able to control news production. This research will try to answer some key questions related to the role of press law in controlling news production in online media in Indonesia, which are contained in the following problem formulation: How does Law No. 40/1999 on the Press regulate news production on online media? What is the impact of press law provisions on freedom of expression in the context of online media? This research uses a statutory approach and a legal concept analysis approach with document analysis strategies and interviews. The effectiveness of press law has been running well. The participation of the public, press workers, press companies and the Press Council in controlling news production is good. The Press Law needs to be improved. Restrictions on the right of refusal need to be included in the provisions of the article in the Press Law.